The Identity of Who/What is Greater than the Temple in Matthew 12:6 - Appiah, John (Ghana journal of religion and theology, 2021)
What is greater than the Temple is an ongoing debate among New Testament (NT) scholars. Scholars interpret what is greater than the Temple either as the kingdom of God/heaven, the superior service of the disciples of Jesus, love/mercy, or Jesus. However, though some of the literature so far reviewed considered Matthew’s usage of comparative adjectives in his Gospel, it is not exhaustive. This article intends to investigate Matthean's style of using the comparative adjective to help interpret the one on 12:6. This article uses the text-centred approach of exegesis to unravel the identity of what is greater than the Temple in Matt. 12:6. The study concludes that what is greater than the Temple would be a temple or something relating to the Temple. We conclude that what is greater than the Temple is Jesus’ ministry.